Multimodal imaging diagnosis of pancreatic Castleman disease with abdominal and retroperitoneal lymphadenopathy: a case report and literature review - Jin, Chunchun; Deng, Meifang; Zhang, Jing; Lu, Jianghao; Hao, Yanli (Frontiers in Oncology, 2024)
IntroductionCastleman’s disease (CD) represents a rare polyclonal lymphoproliferative disorder characterized by atypical lymph node hyperplasia, the precise etiology of which remains undefined. Pancreatic involvement of CD is particularly uncommon and often misdiagnosed due to its nonspecific clinical features, making it difficult to distinguish from tumors with abundant blood supply such as solid pseudopapillary tumors and neuroendocrine tumors. Multimodal imaging plays a crucial role in diagnosing pancreatic CD and determining the extent of lymph node involvement. Surgical resection is the preferred treatment for unicentric CD (UCD). Regular follow-up and monitoring are essential for optimal patient management and treatment outcomes.Case PresentationA 26-year-old female presented to our hospital with a pancreatic mass detected during a routine health examination. Physical and laboratory examinations were unremarkable. Conventional ultrasound revealed a hypoechoic, oval-shaped mass measuring approximately 34×31 mm in the pancreatic head, with clear boundaries and heterogeneous internal echoes, but no significant blood flow signals. Contrast-enhanced ultrasound showed hyperenhancement of the pancreatic head mass, raising suspicion for a solid pseudopapillary tumor or other entities. To clarify the diagnosis, Contrast enhanced CT, MRI, and FDG PET-CT were performed. Both Contrast enhanced CT and MRI demonstrated hyperenhancement of the lesion, and PET-CT showed hypermetabolism in the pancreatic head mass, along with multiple enlarged lymph nodes in the abdominal and retroperitoneal regions. These findings suggested a lymph node origin for the pancreatic head mass. Surgical resection was performed, and pathological examination confirmed UCD. The patient has been followed for 44 months without recurrence.ConclusionThis case illustrates the utility of multimodal imaging in diagnosing pancreatic CD. In cases of benign pancreatic lesions with enlarged abdominal and retroperitoneal lymph nodes, CD should be considered.